2018
DOI: 10.1177/0093854818799379
|View full text |Cite
|
Sign up to set email alerts
|

Improving Case Plans and Interventions for Adolescents on Probation: The Implementation of the SAVRY and a Structured Case Planning Form

Abstract: Even when probation officers use risk assessment tools, many of their clients' needs remain unaddressed. As such, we examined whether the implementation of the Structured Assessment of Violence Risk in Youth (SAVRY) and a structured case planning form resulted in better case plans as compared to prior practices (i.e., a non-validated local tool and an unstructured plan). Our sample comprised 216 adolescents on probation who were matched via propensity scores. Adolescents in the SAVRY/Structured Plan condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…More specifically, rather than comparing the ARROW to an entirely unstructured approach to case planning (i.e., a blank space in which to write in a case plan), we compared the ARROW to a short case planning form. In a previous study, we found that this case planning form resulted in significantly better case plans than an entirely unstructured approach (Viljoen et al, 2019). Thus, our goal was to determine if the ARROW could lead to improvements in plans above and beyond an approach that had already achieved some degree of success.…”
Section: Study 2: Field Studymentioning
confidence: 95%
See 3 more Smart Citations
“…More specifically, rather than comparing the ARROW to an entirely unstructured approach to case planning (i.e., a blank space in which to write in a case plan), we compared the ARROW to a short case planning form. In a previous study, we found that this case planning form resulted in significantly better case plans than an entirely unstructured approach (Viljoen et al, 2019). Thus, our goal was to determine if the ARROW could lead to improvements in plans above and beyond an approach that had already achieved some degree of success.…”
Section: Study 2: Field Studymentioning
confidence: 95%
“…To measure the quality of formulations and case plans, we used the ACERR (Viljoen et al, 2019). This tool was developed through a review of recommended practices (e.g., Bonta & Andrews, 2017), expert feedback, and pilot testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers should consider going beyond merely training organization staff about how to complete an assessment instrument or carry out a particular treatment modality and instead help to design and support the implementation effort. Examples of researcher‐guided implementation studies in forensic and justice settings are growing but are still uncommon (see, e.g., Knight et al., 2016; Viljoen, Shaffer, Muir, Cochrane, & Brodersen, 2019, Vincent, Guy, Perrault, & Gershenson, 2016).…”
Section: Researcher‐guided Implementationmentioning
confidence: 99%